AN ANALYSIS OF 2017 ENGLISH AS AN ADDITIONAL LANGUAGE (EAL) EXAMINATION TEST ITEMS FOR VICTORIAN SENIOR HIGH SCHOOL IN TERMS OF THE LEVEL OF QUESTIONS (HOT OR LOT) AND COMMUNICATIVE LANGUAGE ABILITY - Anni Marhamah; Muhammad Ikbal (The Seall Journal, 2020)
This article aimed to observe and analyzed English as an additional language (EAL) examination test items for Victorian senior high school in terms of the level of questions (HOT or LOT) and communicative language ability. This study was conducted due to the importance of providing the appropriate and good test items for students in gaining students’ competence. This study was conducted through qualitative research focusing on the content analysis method. The data source used in this study was document of English as an additional language (EAL) examination test items of Victorian senior high school. The test items were observed, classified, analyzed, and then the results were interpreted and drew the conclusion. This study was done by analyzing the test items document due to the levels of questions and communicative language ability.